BENTUK-BENTUK GAYA BAHASA SINDIRAN PADA FILM COMIC 8 KASINO KING PART 2 KARYA ANGGY UMBARA (ANALISIS STRUKTURAL) - Harbeng Masni; Pitri Yani (Universitas Batanghari, 2019)
The purpose of this study is to describe the forms of satirical language style in the film Comic 8 Casino King Part 2 by Anggy Umbara, which consists of three forms, namely irony, cynicism, and sarcasm. This research is a descriptive qualitative research with a structural approach. The primary data in this study are dialogues relating to satirical language style (irony, cynicism, sarcasm) contained in Comic 8 Movie Casino King Part 2 by Anggy Umbara. Secondary data in this study is a transcript of conversations from Comic 8 Casino King Part 2 by Anggy Umbara. Data were analyzed using the concepts of Tarigan, Keraf, and Purwandi. Based on the results of the analysis research it can be concluded that there are (1) the form of irony satire language style which is a subtle allusion, found in some data including the items, hair smells only, and longish Eh contained in seventeen quotes. (2) Cynicism satirical form of style which is a satire containing ridicule of sincerity and sincerity is found in some data including cowards, sissy, and killer forces contained in five quotations. (3) The form of sarcasm satire language style which is the most crude allusions found in some data including crazy, stupid, and use a little brain contained in eight quotations.